Model Komunikasi Kelompok Tentang Makna Pernikahan Antargenerasi di Kalangan Kelas Menengah Jakarta - Nur Kholisoh; Primayanti Primayanti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
Nowadays the meaning of marriage has changed as found in various phenomena of exiting from state regulations and laws, religion, customs and norms in society. The research aims at finding interaction model and group communication leading to changes of meaning of marriage among inter-generation of middle-class groups in in DKI Jakarta. This research refers to Alfred Schutz teories of symbolic interactionism, group-communication, and social phenomenology. Qualitative research method is used to analyze data completed by depth interview and FGD as data collection technique. The results shows that interaction model on mariage meaning is influenced by the way people grow, interact, and communicate within their group. The meaning of marriage symbols which is exchanged in the interaction of a group has changed from one generation to the next generation. Marriage is perceived as destiny, the unity between man and woman as a way of preserving human beings, justifying sexual intercourse and holding religious order. The research also fond contradictive phenomenon of marriage meaning between marriage meaning with the sacred law of marriage, whether it is in state regulations, customs and norms of society, such as same-sex marriage phenomenon (gay/lesbian), swinging behavior, samen leven, and free sex.